Metabolite systems profiling identifies exploitable weaknesses in retinoblastoma. Issue 1 (27th November 2018) - Sahoo, Swagatika; Ravi Kumar, Ranjith Kumar; Nicolay, Brandon; Mohite, Omkar; Sivaraman, Karthikeyan; Khetan, Vikas; Rishi, Pukhraj; Ganesan, Suganeswari; Subramanyan, Krishnakumar; Raman, Karthik; Miles, Wayne; Elchuri, Sailaja V.
Abstract : Retinoblastoma (RB) is a childhood eye cancer. Currently, chemotherapy, local therapy, and enucleation are the main ways in which these tumors are managed. The present work is the first study that uses constraint‐based reconstruction and analysis approaches to identify and explain RB‐specific survival strategies, which are RB tumor specific. Importantly, our model‐specific secretion profile is also found in RB1‐depleted human retinal cells in vitro and suggests that novel biomarkers involved in lipid metabolism may be important. Finally, RB‐specific synthetic lethals have been predicted as lipid and nucleoside transport proteins that can aid in novel drug target development. Abstract :